Characterization of a foodborne outbreak caused by Salmonella Enteritidis in Aracaju, State of Sergipe, Brazil - Maria Regina Pires Carneiro; Pedro Hernan Cabello; Ricardo Luiz Cavalcanti Albuquerque-Junior; Sona Jain; Alexandre Luna Candido (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
INTRODUCTION: In December 2001, an outbreak of foodborne gastroenteritis infected 114 of 161 people who ate at a restaurant in Aracaju, State of Sergipe, Brazil. METHODS: The epidemiological and microbiological aspects of the outbreak were characterized. RESULTS: Potato salad made with homemade mayonnaise and stored at unsuitable temperatures was associated with increased risk of foodborne infection. Salmonella Enteritidis was isolated from the diarrheal stools of the hospitalized patients, and genotyping of the fecal samples generated identical randomly amplified polymorphic deoxyribonucleic acid (DNA) profiles. CONCLUSIONS : To the best of our knowledge, this is the first and the only record of a gastrointestinal outbreak in Sergipe.